Dampak Sosial-Ekonomi Kemitraan KUD Tani Makmur dengan PT. Nestle Indonesia (Studi Kasus di Desa Kandang Tepus, Kecamatan Senduro, Kabupaten Lumajang) - LUKY AISYAH ANDRIANI; I WAYAN WINDIA; I NYOMAN GEDE USTRIYANA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
Socio-Economic Impact Partnership KUD Tani Makmur with PT. NestleIndonesia (Case Study in Kandang Tepus Village, Senduro Sub-District, Lumajang Regency)One form of relationship between subsystems in the agribusiness system is the relationship between dairy farmers, dairy cow cooperatives, and the Milk ProcessingIndustry (IPS). One of the dairy cow milk cooperatives in partnership with IPS is theKUD Tani Makmur in Kandang Tepus Village, Senduro District, Lumajang Regency.KUD Tani Makmur in running his dairy cow business in partnership with PT. NestleIndonesia.The partnership between KUD Tani Makmur and Nestle is contractual, inwhich this partnership impacts socially and economically for cooperatives. The purposeof this study was to determine the social and economic impacts of KUD Tani Makmurbecause they partnered with Nestle.The research method used for social impact isqualitative. Whereas for economic impacts quantitative analysis and trend analysis areused. The results of the analysis show that there is a change in knowledge, attitudes, andactions of cooperative employees and members. This change is positive. In addition,there are changes in positive social values and norms and institutions. The economicimpact obtained is also positive, the cooperative has increased income, the number of members of the cooperative, the development of physical cooperatives. The SHUobtained by cooperatives in the 2013-2016 period fluctuated, which in 2015 experienceda decline. This extension is due to the lack of proper implementation of cooperativestrategies in dealing with competitors. The positive impact of social and economicneeds to be maintained, while to overcome competitors need to know the weaknessesand strengths of competitors so as not to implement a strategy that is inappropriate.